The Role of Audio-Visual Tools in Enhancing Secondary School Students' Proficiency in Arabic Reading - Muhammad Shukri Abdul Halim; Nazri Atoh (Bumi Lingua Edu Center, 2025)
Audio-visual tools play a vital role in supporting a more interactive and effective teaching and learning process, particularly in mastering Arabic reading skills. This research aims to evaluate the impact of audio-visual tools on reading proficiency among secondary school students. Traditional reading instruction often fails to sustain students’ interest and attention; hence, technology-based approaches are believed to stimulate multiple senses and enhance active student engagement. This quantitative research employed a survey design involving 92 Form Two students from one of the Islamic secondary schools in Perak, Malaysia. A five-point Likert-scale questionnaire was used to assess students’ perceptions of the effectiveness of audio-visual materials in reading activities. The findings revealed highly positive student perceptions, with mean scores ranging from 3.95 to 4.22. These tools not only increased students' interest and motivation but also supported text comprehension, improved pronunciation, and reinforced memory retention of reading content. Overall, the use of audio-visual materials is proven to be a practical and relevant pedagogical approach in addressing the learning needs of the 21st century. This research recommends the systematic integration of audio-visual tools in Arabic language instruction at a global level.